Motor's low voltage protection method and apparatus - QIAN ZHIHONG; QIN WENJIE; SHI ZHENTANG; WANG LE; DU HONGYONG; MENG FANZHONG (2017)
The invention discloses a motor's low voltage protection method and an apparatus, comprising: when a power grid voltage is reduced, after a first preset time, comparing the motor terminal voltage with the locked-rotor voltage; if the motor terminal voltage is smaller than the locked-rotor voltage, then, tripping; after a second preset time, conducting switch closing again; then, comparing the motor terminal voltage with the locked-rotor voltage again; if the motor terminal voltage is greater than the locked-rotor voltage, starting the motor; and if the motor terminal voltage is smaller than the locked-rotor voltage, stopping the motor. According to the invention, the method and the apparatus are able to cut off a motor that cannot work normally so as to protect the stable operation of other motors and the power grid. 本发明公开了种电动机低电压保护方法及装置，包括：当电网电压降低时，经过第预设时间后比较电动机的机端电压与堵转电压值，若机端电压小于堵转电压值，则跳闸；经过第二预设时间后，重新合闸；再次比较机端电压与堵转电压值，若机端电压大于等于堵转电压值，起动电动机；若机端电压小于堵转电压值，停止电动机。本发明可以及时切除不能正常运行的电动机，保护其他电机和电网的稳定运行。